Heat Flow, Geotherms, Density and Lithosphere Thickness in SW of Iberia (South of Portugal)” - Duque, Maria Rosa (2019)
Thermal structure, density distribution and lithosphere thickness in the SW part of the Iberian Peninsula are studied using data obtained in the South Portuguese Zone (SPZ) and SW border of the Ossa Morena Zone (OMZ) in the South of Portugal. Five different regions were defined, and models were built for each region. Geotherms were obtained using average density values from data published. The high values of heat flow density in these regions are attributed to occurrence of anomalous heat sources due to radioactivity content and exothermic chemical reactions associated to ore deposits in the zone. The results obtained with models based on isostasy in the region led to lithosphere thickness values between 95 and 96 km in the SPZ and a lower value of 94.5 km in the SW border of the OMZ. Analysis of geotherms shows lateral variations of temperature at the same depth. These lateral variations are compared with information obtained with seismic data.